The duty of care for negligents misstatements / A. Razak Salleh - Salleh, A. Razak (Faculty of Law, 1986)
As part of the requirement for the obtainment of the Diploma in Law, every Law students who are in their final semester are require to do a Project Paper. The topic for the Project Paper are chosen by the students themselves on condition that it get approval from the School of Law. I have chosen the topic of Duty of Care for Negligents Misstatements, because I find that the topic is very fascinating and there is a lot of material been written about the topic. In writing the topic I was compelled to look at English and commonwealth sources, especially those of Australia. I have try to keep a proper balance between the need to discuss the topics considered essential and to keep the 'paper' to a reasonable length.